A Runic Prayer - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2011)
Contrary to modern view of the runes as symbols and bearers of pagan traditions, the mediaeval runic inscriptions found in Scandinavia bear witness of making use of the indigenous alphabet to serve the new religion, Christianity. In this paper a number of inscriptions are analyzed with respect to the prayer formula that typically is a part of a text commemorating the dead. Different runic masters are found to have been more or less theologically educated in the tenets of the new religion. The prayer formulas show a changing society, reorienting from the pagan traditions towards the christian ones.